Cambodian students' motivation in the learning English language: A small-scale survey at a private high school in Phnom Penh - Sereyrath Em; Minea Yun; Brak Dorn; Vannak Sao; Pheara Sin (Universitas Islam Malang, 2022)
English has become the world's language, and it has been used by many people in different countries as a means of international communication. Motivation to learn English has been seen as the most important factor contributing to the success of students' learning. The current study employed a quantitative design and was conducted to find out the motivation levels of students studying English as a foreign language at a private high school in Phnom Penh. 60 students participated in a survey after we sought agreement from school principals and teachers of English there. The findings show that the students in the studied context were more extrinsically motivated to learn English rather than intrinsically. The sum of intrinsic and extrinsic motivations also revealed students' moderate motivation to learn English. Due to the small scale of the survey study, a future study should be conducted with larger sample size and at other educational institutions across Cambodia. Qualitative and mixed-methods designs are also highly recommended.